2018
DOI: 10.1155/2018/5194016
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacological Approach to Investigate the Mechanism of Acori Tatarinowii Rhizoma for Alzheimer’s Disease

Abstract: In traditional Chinese medicine (TCM), Acori Tatarinowii Rhizoma (ATR) is widely used to treat memory and cognition dysfunction. This study aimed to confirm evidence regarding the potential therapeutic effect of ATR on Alzheimer's disease (AD) using a system network level based in silico approach. Study results showed that the compounds in ATR are highly connected to AD-related signaling pathways, biological processes, and organs. These findings were confirmed by compound-target network, target-organ location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 101 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…The primary active fraction of ATR is the essential oil. ATEO was reported to exert a neuroprotective effect in neurological disorders, including in neuroprotection on antioxidation, anti-inflammation and neurotrophic function [12][13][14][15]. The quality of ATEO varies widely due to region difference; however, little is known about how to study ATEO quality chemically and biologically in response to region difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary active fraction of ATR is the essential oil. ATEO was reported to exert a neuroprotective effect in neurological disorders, including in neuroprotection on antioxidation, anti-inflammation and neurotrophic function [12][13][14][15]. The quality of ATEO varies widely due to region difference; however, little is known about how to study ATEO quality chemically and biologically in response to region difference.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity assays studied in this work included regulation of anti-oxidative proteins (GPx1, SOD2 and UCP2), neurotrophic factors (NGF, BDNF and GDNF) and pro-inflammatory cytokines (IL-1β, IL-6 and TNFα). The up-regulation of anti-oxidative proteins (GPx1, SOD2 and UCP2) and inhibition of pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) could protect neurons against damage caused by injury, oxidative stress and inflammation, while the induction of neurotrophic factors could promote neuroregeneration [14,43]. Our results indicated that ATEO exhibited anti- oxidative, anti-inflammatory and neurotrophic effects which were supported by previous findings that ATEO protected H 2 O 2 -induced cell injury via CREB/PGC-1α activation in PC12 cells and induced the expression of neurotrophic factors by protein kinase A (PKA) in cultured astrocytes [15,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All networks were visualized using Cytoscape software (version 3.7.1) [88]. e target location network was generated based on the analysis of gene expression data of various hematopoietic tissues and organs obtained from e Human Protein Atlas [89] and BioGPS databases [90]; this network was generated by linking the target to the corresponding tissues and organs where it was analyzed to be specifically expressed using previously described procedures [91][92][93][94][95][96][97][98]. e protein-protein interaction (PPI) network was constructed using the STRING database (version 11.0) [99] and interactions with highest confidence scores (≥0.9) were selected for further analysis.…”
Section: Construction Of Smt-associated Networkmentioning
confidence: 99%
“…To understand the therapeutic effects of SMT at the tissue-and organ-level, we generated a target location network based on the gene expression data for individual myelosuppression-associated SMT targets across various tissues and organs, which were identified from e Human Protein Atlas [88] and BioGPS databases [90] and analyzed as previously described [91][92][93][94][95][96][97][98] (Figure 5; see Materials and Methods). Consequently, we found that the targets were expressed in various hematopoietic tissues and organs [129,130], including the liver (degree = 144), bone marrow (degree = 137), spleen (degree = 116), lymph nodes (degree = 113), and blood (degree = 100) ( Figure 5), which suggests the systematic mechanism of action responsible for the pharmacological effects of SMT.…”
Section: Network-based Analysis Of the Pharmacological Mechanisms Of mentioning
confidence: 99%